Quantitative data analysis in communication research: second edition / Ahlam Abdul Aziz, Zaridah Abdullah and Antashah Mohd Nor - Abdul Aziz, Ahlam; Abdullah, Zaridah; Mohd Nor, Antashah (UiTM Press, 2022)
With a deep sense of gratitude to Allah the Almighty, we proudly present the second edition of the Quantitative Data Analysis in Communication Research book. The book is written carefully to help Mass Communication students understand the concepts and applications of statistical procedures for data analysis. This book initially contains four chapters. Each chapter explained how to analyze the data step by step through manual calculations and SPSS procedures so that students will be proficient in both methods. The statistical analyses which are covered in this book are the parametric and non-parametric tests such as the one-sample, independent sample and paired sample f-test, one-way ANOVA, Pearson Correlation, and Chi-Square test. For the second edition, the authors have added one unit, which is Statistical Notation. With the addition of this unit, it is hoped that students will be able to review the basic mathematical procedures they have learned in their secondary schools. The authors also add more exercise questions for students to practice. For these reasons, we hope that this book will assist students in their research courses.